Perceived collaborative risk in small and medium technology enterprises. (4th March 2023) - Klimczak, Karol Marek; Machowiak, Wojciech; Shachmurove, Yochanan; Staniec, Iwona
ABSTRACT: We study risk perceived by small and medium technological enterprises (SMTEs) in their collaborative activities. We aim to explain prior findings regarding the situational factors that shape collaborative activities by focusing on assessments of risk made by managers. This study confirms that trust, business performance, and environmental turbulence affect the level at which managers assess risk. Trust and turbulence lower the assessment of collaborative risk, increasing the willingness to collaborate. In contrast, business performance increases perceived risk and potentially reduces manager's willingness to collaborate. The article contributes to studies of technological collaboration and management practice.